100% renewable energy for Germany: Coordinated expansion planning needed - Leonard Göke; Claudia Kemfert; Mario Kendziorski; Christian R. von Hirschhausen (DIW Weekly Report, 2021)
Due to ambitious climate change targets and other energy and industrial policy goals such as the nuclear phase-out, the energy transition in Germany is heading toward a completely renewable energy system. This Weekly Report is the first to describe scenarios for 100 percent renewable energy coverage in Germany and, furthermore, shows it is both possible and realistic. In such a scenario, no more fossil fuels or nuclear energy would be used throughout Europe. With the available potentials, both electricity demand and overall energy demand can be covered by renewable energy. Due to electrification and sector coupling, electricity demand has doubled to around 1,200 terawatt hours. However, there have also been significant efficiency increases in the transportation and heating sectors. By taking grid expansion costs into account, power generating structures that are close to the load center would be strengthened compared to their state as of 2021. Despite more decentralized generation and storage structures, supply security would be guaranteed by integration into the European power grid. The perspective of a completely renewable energy system must be included in the planning of the entire energy system, including 100 percent renewable energy scenarios in German and European grid planning.
Keywords: Q54; L94; 330; Renewable energy; sector coupling; energy planning